Aggregates of diketopyrrolopyrrole dimers in solution. (January 2017) - Wawrzinek, Robert; Zhou, Xiuwen; Ullah, Mujeeb; Namdas, Ebinazar B.; Lo, Shih-Chun
Abstract: Dimers based on diketopyrrolopyrrole (DPP) chromophores have gained tremendous interest as an excellent material building block for organic solar cells and photodiodes. However, a counterintuitive blue-shift in their solution absorption spectra occurs with an increasing number of thiophene units bridging the DPP moieties. We allocate this to aggregates in solution, which might hinder adequate mixing in blends, leading to poor film forming quality and reduced charge generation in solution processed devices. Hence, identification of such aggregates is crucial in order to find measures for device optimisation. In this study, we present synthesis and characterisation of three pyridyl end-capped DPP dimers of different conjugation length using thiophene linkers and compare their parent monomer to evidence the behaviours of aggregates in solution. We employ conventional and temperature dependent UV–Vis spectroscopy, fluorescence and excitation-emission spectroscopy as well as TD-DFT calculations to show that such DPP dimers predominantly form aggregates in solution even at low concentrations. By disentangling the spectroscopic behaviour of both aggregated and non-aggregated species, we refute literature's explanation that the apparent blue shift in absorption arises from a reduced conjugation length due to more molecular flexibility. Instead, absorption and emission signals of non-aggregated dimers are mostly masked by their aggregated species. This work provides a tool set using common laboratory spectroscopic equipment to identify and characterise solution aggregates—information particularly important towards optimisation of organic electronics processed from solution. Graphical abstract: 3D excitation-emission spectroscopy disentangles the spectroscopic properties of aggregates and non-aggregates of DPPs based dimers, Robert Wawrzinek, Xiuwen Zhou, Mujeeb Ullah, Ebinazar B. Namdas, and Shih-Chun Lo. Highlights: A DPP monomer and three thiophenyl bridged DPP dimers are described. Solution aggregates of dimers show unusual blue shifted absorption trend. Aggregates mask spectroscopic properties of non-aggregated species. 3D excitation-emission spectroscopy enables identification of solution aggregates.